Tail Risk Concerns Everywhere - Gao, George P.; Lu, Xiaomeng; Song, Zhaogang (Management Science, 2019)
We show that the beta with respect to an index of global ex ante tail risk concerns (𝔾ℝ𝕀𝕏), which we construct using out-of-the-money options on multiple global assets, negatively drives cross-sectional return variations across asset classes, including international equity indices, foreign currencies, and government bond futures. The pricing power of 𝔾ℝ𝕀𝕏 becomes stronger when more asset-class-level tail risk concerns are incorporated in the index construction. 𝔾ℝ𝕀𝕏 also dominates asset-class-level tail risk concerns in pricing assets within each asset class. These evidences imply that the pricing effect of tail risk concerns works predominantly as a global channel. The 𝔾ℝ𝕀𝕏 pricing effect is distinct from that of tail risk factors based on historical realizations, consistent with the interpretation that tail risk concerns likely reflect investors’ ex ante subjective belief about tail risk. This paper was accepted by Neng Wang, finance.